Comparison of Uterine Artery Dynamics in Normotensive and Hypertensive Pregnancies on Doppler Ultrasound - Mishal Asif, Syed Muhammad Yousaf Farooq, Talha Saleemee, Muhammad Talha Asif, Zartash Gull, Hafsa Talat, Taiba Suleman, Ayesha Mudassar, Muhammad Kamran, Irfan Ullah, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Hypertension during pregnancy is a common disease that can alter the health of both mothers and fetus. It is a leading cause of maternal, fetal, and neonatal death, as well as an increased risk of having an undesirable pregnancy outcome. Objective: To compare uterine artery dynamics in normotensive and gestational hypertensive pregnancies on Doppler ultrasound. Methodology: A cross-sectional case control study was carried out in Radiology department of District Head Quarter (DHQ) hospital, Faisalabad. Written consent was taken from all patients before the ultrasound examination. The calculated sample size was 98. Patients were assessed for eligibility in inclusion criteria. Confirmation of intrauterine living pregnancy and gestational age was done with routine obstetric ultrasound. Enrolled pregnant patients both normal and hypertensive were assessed for uterine artery Doppler ultrasound examination. Results: Ninety eight women, forty-nine with hypertension and forty-nine normal women participated in the investigation. The comparison of data showed that pre pregnancy weight and mean blood pressure were significantly high in hypertensive group when compared to the normotensive group (P <0.05). Doppler ultrasound also showed that the values of uterine artery parameters such as S/D Ratio, PI, RI was significantly high in hypertensive group when compared to the normotensive group (P <0.05). Conclusion: The Uterine artery Doppler parameters are significantly higher in hypertensive patients as compared to normotensive patients. According to the findings of our study, notching on the right, left, or bilateral, as well as Pulsatility index and Resistivity Index, are diagnostic parameters for evaluating the complications before they worsen. Keywords: Uterine artery, Gestational hypertension, Doppler Ultrasound, Doppler Indices, Pre-Eclampsia